Effectiveness of palivizumab in children with childhood interstitial lung disease: The French experience. Issue 7 (4th December 2015) - Drummond, David; Thumerelle, Caroline; Reix, Philippe; Fayon, Michael; Epaud, Ralph; Clement, Annick; Mahloul, Malika; Habouria, Delphine; Delacourt, Christophe; Hadchouel, Alice
Summary: Introduction: There is a lack of evidence concerning the effectiveness of immunoprophylaxis with palivizumab in children with childhood interstitial lung disease (chILD). In this retrospective study, we evaluated the effectiveness of palivizumab for decreasing the rate of RSV‐related hospitalizations in children under the age of 24 months with chILD treated with corticosteroids. Methods: A retrospective national study was conducted in France. Patients born between 2007 and 2013, diagnosed with chILD and on corticosteroid treatment were identified through the French online database for pediatric interstitial lung disease (Respirare ® ). Data were collected for the etiology and severity of chILD, risk factors and preventive measures for bronchiolitis, palivizumab immunoprophylaxis, and hospitalizations for bronchiolitis and RSV‐bronchiolitis. Results: We included and evaluated 24 children during their first two RSV seasons, corresponding to 36 patient‐seasons. The observed rate of RSV‐related hospitalization (305/1000 patient‐seasons), and the median length of stay (7 days), were higher than those for the general population. RSV‐related hospitalization rates did not differ significantly between children with and without palivizumab prophylaxis (5/16 vs. 4/18, respectively, P  = 0.70). Conclusion: Children with chILD on corticosteroid treatment are at high risk of hospitalization for RSV‐bronchiolitis, which tends to be more severe in these children than in the general population. The effectiveness of palivizumab prophylaxis in this population remains to be demonstrated.Pediatr Pulmonol. 2016;51:688–695 . © 2015 Wiley Periodicals, Inc.